Revoking Citizenship : Expatriation in America from the Colonial Era to the War on Terror - Herzog, Ben (Social science teacher) (Book collections on Project MUSE., 2015)
Revoking citizenship has been an official part of American policy since the end of the nineteenth century. This book sheds light on the current state practice by looking at its transformation in the United States from the colonial era to the War on Terror. Not limited to a legal studies perspective, it also places the revocation of citizenship within the framework of historical sociology.